Research on Limitation of Snake Flow Test in Routers' Performance Test - Liang Guo; Subin Wang; Junqi Zhao; Hua Chen (Dianxin kexue)
Fully-mesh topology test ＆ snake topology test methods on high port density routers were presented. The differences of the test results in latency, jitter, drop, traffic model and so on, were analyzed. The limitation of snake flow test methods in performance test was revealed.